Flexible Multi‐Material Fibers for Distributed Pressure and Temperature Sensing. (3rd January 2020) - Yu, Li; Parker, Steven; Xuan, Haifeng; Zhang, Yujing; Jiang, Shan; Tousi, Maryam; Manteghi, Majid; Wang, Anbo; Jia, Xiaoting
Abstract: With the recent development of wearable electronics and smart textiles, flexible sensor technology is gaining increasing attention. Compared to flexible film‐based sensors, multimaterial fiber‐based technology offers unique advantages due to the breathability, durability, wear resistance, and stretchability in fabric structures. Despite the significant progress made in the fabrication and application of fiber‐based sensors, none of the existing fiber technologies allow for fully distributed pressure or temperature sensing. Herein, the design and fabrication of thermally drawn multi‐material fibers that offer distributed temperature and pressure measurement capability is reported. Thermoplastic materials, thermoplastic elastomers, and metal electrodes are successfully co‐drawn in one fiber. The embedded electrodes inside the fibers form a parallel wire transmission line, and the local characteristic impedance is designed to change with the temperature or pressure. The electrical frequency domain reflectometry is used to interrogate the impedance change along the fiber and provides information with high spatial resolution. The two types of fibers reported in this manuscript have a pressure sensitivity of 4 kPa and a temperature sensitivity of 2 °C, respectively. This work can pave the road for development of functional fibers and textiles for pressure and temperature mapping. Abstract : Flexible multi‐material fibers with distributed temperature and pressure sensing capability are fabricated by the thermal drawing technique. Frequency domain reflectometry is used to interrogate the fibers to provide high spatial resolution sensing capability. A temperature resolution of 2 °C and pressure resolution of 4 kPa are achieved by the two types of fibers.